ChemInform Abstract: CuI/Glycerol Mediated Stereoselective Synthesis of 1, 2‐Bis‐chalcogen Alkenes from Terminal Alkynes: Synthesis of New Antioxidants. Issue 10 (March 2015) - Goncalves, Loren C. C.; Victoria, Francine N.; Lima, David B.; Borba, Pedro M. Y.; Perin, Gelson; Savegnago, Lucielli; Lenardao, Eder J.
Abstract The Zn/CuI/glycerol‐reaction system is recovered and reused in five additional cycles with slightly decreasing yields.